Corporate income tax compliance costs of small and medium enterprises in Thailand - Chunhachatrachai, Papaporn (Curtin University, 2013)
This thesis is the first attempt to estimate tax compliance costs of Small and Medium Enterprises (SMEs) in Thailand. A mixed methodology approach has been used divided into two phases: phase I is the major quantitative phase, followed by a minor qualitative phase II. The findings demonstrate that tax compliance costs are a significant burden and a hidden cost upon SMEs in Thailand. A better tax policy to reduce tax compliance costs is recommended.